ANALISIS KONTRASTIF DALAM PEMBELAJARAN BAHASA (Kajian Antara Konsonan-Vokal Pada Huruf Hijaiyah dan Alpabet Indonesia) - Zahara Kamsir, Rita (Jurnal Sakinah, 2020)
Contrastive analysisis activity to compare a language to identify similarity and difference to get using contrastive as principle to predict language learning difficulties. The similarity of alphabetic pronunciation between Arabic and Indonesia can support Arabic learning or second languange. Meanwhile, the different can cause difficulties to learn in. First language habit influence consonant sound and further vocal language, so it need contrastive analysis (difference) both Arabic and Indonesia.